Visualization of Hg2+ Stress on Plant Health at the Subcellular Level Revealed by a Highly Sensitive Fluorescent Sensor - Sumeera Asghar; Zhenyang Yu; Zheng Zhu; Dengyue Zheng; Zimo Zhao; Yuming Xu; Xiao Liu; Chao Yuan; Yan Li; Wei Wang; Jianfeng Xu; Huailong Teng; et al. (Research)
The presence of Hg2+ causes substantial stress to plants, adversely affecting growth and health by disrupting cell cycle divisions, photosynthesis, and ionic homeostasis. Accurate visualization of the spatiotemporal distribution of Hg2+ in plant tissues is crucial for the management of Hg pollution; however, the related research is still at its early stage. Herein, a small-molecule amphiphilic fluorescent probe (termed LJTP2) was developed for the specific detection of Hg2+ with a high sensitivity (~16 nM). Fluorescent imaging applications with LJTP2 not only detected the dynamic distribution of Hg2+ within plant cells at the subcellular level but also enabled the understanding of cell membrane health under Hg2+ stress. This study introduces a valuable imaging tool for elucidating the molecular mechanism of Hg2+ stress in plants, demonstrating the potential of the application of small-molecule fluorescent probes in plant science.